Beneficial Use of Water Treatment Sludge with Stabilizers for Application in Road Pavements - Takao, Túlio W. [UNESP]; Bardini, Vivian S.; de Jesus, Amanda D. [UNESP]; Marchiori, Leonardo; Albuquerque, Antonio; Fiore, Fabiana A. [UNESP] (MDPI, 2024)
Water treatment sludge (WTS) is the residue produced during water treatment processes for public use. Exploring the reintroduction of these wastes into the production chain to generate new, value-added materials presents a current challenge. This could promote their reuse and reduce the negative environmental impacts associated with their disposal. This study assessed the technical feasibility of using aluminum-based WTS to partially replace silty sand soil in mixtures that include two stabilizers (hydrated lime and Portland cement), potentially for use in road pavements. After conducting a thorough physical, chemical, and geotechnical characterization of both the soil and the sludge, bench-scale experiments were carried out to test the mixtures’ resistance, with WTS proportions of 5%, 8%, 10%, 15%, and 20%, stabilized with either lime or cement. The findings confirm that WTS does not contain potentially toxic elements, according to Brazilian standards, and all tested composites appear suitable for paving. However, the mechanical resistance of the soil–sludge–cement mixtures decreases as the WTS content increases, with an optimum California bearing ratio (CBR) of 41.50% achieved at a 5% WTS addition. Meanwhile, incorporating 15% WTS into soil–sludge–lime mixtures resulted in the highest CBR value of 21.25% for this type of mixture. It is concluded that incorporating stabilizers into soil–WTPS mixtures for road construction allows for an increased percentage of WTPS in silty-sandy soils. Further studies are recommended with different soil types and the addition of fibers to the mixes, to assess the long-term performance of the structure, along with economic and environmental analyses.
Keywords: cement; geotechnical characterization; lime; stabilizing materials; water treatment sludge